Improving English Speaking Ability through Vlogging: an Innovative Breakthrough for Suburban Beginner Learners in English Community Muara Bungo - ridho kurniawan; Susi Susanti (Universitas Muhammadiyah Muara Bungo, 2019)
Speaking skill has a very important role in this era to help students to communicate and to show their understanding in English. This speaking ability can help students to achieve higher academic goals or improve their soft skills to face the challenges in globalization. English Language Study Program of STKIP Muhammadiyah Muara Bungo tries to help the students to solve their Speaking problem by establishing a community which called the English Community. This study aimed to improve students’ speaking abilityin Muara Bungo through Vlogging. This model was chosen because they liked to play gadgets and were more interested in doing many activities with their gadgets. This research was classroom action research. The population in this study were all students who joined as members of the English community. The sample in this study was taken by using total sampling. This research was conducted in three cycles. The results of the first cycle shown that students started speaking by learning ways and techniques of using Vlogging. In the second cycle, students began to be interested in using Vlogging to learn speaking and began practicing speaking through Vlogging. In the third cycle, students were able to practice speaking in a fun way through Vlogging. Based onthe results of interviews with students, they stated that speaking through vlogging was fun, they could become millennial humans that could speak English. By learning to use Vlogging they get two things, namely the ability to speak English and the ability to use Vlogging. In conclusion, Vlogging could improve students' ability in Speaking.